expressive modulation in calligraphic configurations: محمد راضي غضب-علي عبد الحسين محسن (Al-Academy, 2020)
The follower of the art of Arabic calligraphy accurately identifies three prominent dimensions that have framed the dimensions of this art, the functional dimension and the aesthetic dimension, the last of which is the expressive dimension, as it is an art that does not exhaust its aesthetic and indicative purposes because of its possibilities and characteristics that help it to form with any entity designed by calligrapher, with the expressive dimension of the most important of those The dimensions that can be studied within multiple variables, the most important of which are the significance of the text, the spatial and formal organization of the calligraphic functions and the power of the idea from which the calligraphic formation emerges, The formation of an expressive nature is built in the light of the characteristic of modulation and the concepts and concepts that constitute an essential basis for the birth of the expressive dimension. Research subject tagged with (expressive modulation in calligraphic configurations).